Pemodelan Struktur Pori Dari Batuan Geologi Dengan Fractal - Ferani, S (BERKALA FISIKA, 2010)
Has done modeling with fractal pore structure and fracture of geology rock. Sun and Koch (1998)[2] states that the geological formations of porous rock has a fractal nature ..Modeling the generated fractal porous media have been carried out, which generated fractal modeling has the potential high enough to be able to model the porous media, although the modeling parameters require optimization in order to generate fractal porous media a valid model with actual data. The studied rock samples taken from surface rock formations Parigi Cirebon, West Java. Fractal model is then validated by optimizing the parameters that appear in the modeling for valid with the data of rock that can be estimated by image analysis. Key words: fractal, models, rock geology